2022
DOI: 10.1257/aer.20201157
|View full text |Cite
|
Sign up to set email alerts
|

The Human Side of Structural Transformation

Abstract: We document that nearly half of the global decline in agricultural employment was driven by new cohorts entering the labor market. A new dataset of policy reforms supports an interpretation of these cohort effects as human capital. Using a model of frictional labor reallocation, we conclude that human capital growth led to a sharp decline in the agricultural labor supply, accounting, at fixed prices, for 40 percent of the decrease in agricultural employment. This aggregate effect is halved in general equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“… Note that this number is substantially smaller than the average agricultural employment share in 1939. This is consistent with Porzio, Rossi, and Santangelo (2021), which showed that changes in employment shares across cohorts explain a large share of the structural transformation. …”
supporting
confidence: 91%
See 1 more Smart Citation
“… Note that this number is substantially smaller than the average agricultural employment share in 1939. This is consistent with Porzio, Rossi, and Santangelo (2021), which showed that changes in employment shares across cohorts explain a large share of the structural transformation. …”
supporting
confidence: 91%
“…Note that this number is substantially smaller than the average agricultural employment share in 1939. This is consistent withPorzio, Rossi, and Santangelo (2021), which showed that changes in employment shares across cohorts explain a large share of the structural transformation.18 The secular decline in agricultural and manufacturing employment for both natives and refugees in the post-war period reflects the process of structural change toward the service sector. In Section OA-2.4 in the Online Appendix, I analyze these data in more detail.…”
supporting
confidence: 82%
“…Hobijn et al (2018) document disparities in sectoral allocations of workers across cohorts in the US, and Adao et al (2020) in Germany. Porzio et al (2020) report similar patterns across countries in different stages of development. These differences could be caused by broader processes of de-industrialization, as emphasized by Rodrik (2016) and Huneeus and Rogerson (2020).…”
Section: A Simple Theoretical Framework and Open Questionsmentioning
confidence: 60%
“…Ngai and Pissarides, 2007) or capital deepening and factor intensity differences across sectors (Acemoglu and Guerrieri, 2008). Alternative recent theories for the structural transformation process have also emphasized the roles of international trade (Matsuyama, 2009;Uy et al, 2013;Cravino and Sotelo, 2019), home production (Buera and Kaboski, 2012), and changes in the labor supply driven by changes in schooling (Porzio et al, 2020), or by cohort-specific occupational choices (Cociuba and MacGee, 2018;Hobijn et al, 2018). We contribute to this literature by quantifying a complementary demand-side mechanism for the structural transformation process.…”
Section: Introductionmentioning
confidence: 94%